Cyclizine‐induced proinflammatory responses through Akt‐NFκB pathway in macrophages - Wu, Hao‐Min; Chiang, Chen‐Yu; Chen, Wen‐Ying; Chen, Chun‐Jung; Tseng, Ching‐Chi; Chang, Yu‐Chi; Cheng, Wen‐Min; Kuan, Yu‐Hsiang (Environmental toxicology, 2023)
Cyclizine exhibits sedation and treatment of nausea, vomiting, and motion sickness due to antihistaminic and antimuscarinic effects. Cyclizine has the potential for abuse due to the hallucinogenic and euphoric effect. The response of overdose and illegal abuse of cyclizine includes confusion, tremors, chest pain, ataxia, seizures, and lead to suicide. Macrophage plays the important role in the innate immunity. However, over activation of macrophages results in pro‐inflammatory responses in peripheral tissues. In the present study, cyclizine was found to enhanced the generation of pro‐inflammatory cytokines, including tumor necrosis factor (TNF)‐α, interleukin (IL)‐1β, and IL‐6. We further found that secretion of nitrogen oxide (NO) induced by cyclizine via expression of inducible nitric oxide synthases (iNOS). Cyclizine exhibited parallel stimulation of phosphorylation of nuclear factor‐κB (NFκB) p65, and its up‐stream factor Akt. These results indicated that the expression of pro‐inflammatory cytokines, pro‐inflammatory mediators, and adhesion molecules would be induced by cyclizine via activation of Akt‐NFκB pathway in macrophages.